Numerical Literacy and Math Self-Concept: Children-Friendly Learning in Inclusive Elementary Schools - Danuri; Padrul Jana; Bahtiyar Heru Susanto; Averos Iswanda (Universitas Pendidikan Ganesha, 2025)
Numerical literacy refers to the knowledge and ability to use various numbers and basic mathematical symbols to solve problems, while math self-concept means the assessment of students’ skills, abilities, enjoyment, and interest in the subject. However, children with special needs (ABK) and normal students in inclusive Elementary Schools are yet to sufficiently acquire learning that accommodates literacy and math’s self-concept. This causes a need for the implementation of a children-friendly learning process. Therefore, this study aimed to identify the factors influencing the numeracy level and math self-concept, and also explore the obstacles in implementing children-friendly learning in order to facilitate students’ abilities. A qualitative method was applied because of in-depth data exploration regarding children with special needs, while the utilized instruments include tests, questionnaires, and interviews. Both the data collected and the analysis are qualitative, which are obtained through excavation, identification, and description. Consequently, this paper was able to (1) describe the factors influencing the numeracy level and math self-concept in inclusive Elementary Schools, (2) explore the barriers to implementing children-friendly learning, and (3) identify the relationship between students’ numeracy and math self- concept. It can be concluded that effective teaching strategies and a supportive learning environment are essential for improving numeracy and mathematics self-concept among students in inclusive settings.